What Is Learned in Pavlovian Conditioning in Crickets? Revisiting the S-S and S-R Learning Theories - Mizunami, Makoto (Frontiers in Behavioral Neuroscience, 2021)
In Pavlovian conditioning in mammals, two theories have been proposed for associations underlying conditioned responses (CRs). One theory, called S-S theory, assumes an association between a conditioned stimulus (CS) and internal representation of an unconditioned stimulus (US), allowing the animal to adjust the CR depending on the current value of the US. The other theory, called S-R theory, assumes an association or connection between the CS center and the CR center, allowing the CS to elicit the CR. Whether these theories account for Pavlovian conditioning in invertebrates has remained unclear. In this article, results of our studies in the cricket Gryllus bimaculatus are reviewed. We showed that after a standard amount of Pavlovian training, crickets exhibited no response to odor CS when water US was devalued by providing it until satiation, whereas after extended training. they exhibited a CR after US devaluation. An increase of behavioral automaticity by extended training has not been reported in Pavlovian conditioning in any other animals, but it has been documented in instrumental conditioning in mammals. Our pharmacological analysis suggested that octopamine neurons mediate US (water) value signals and control execution of the CR after standard training. The control, however, diminishes with extension of training and hence the CR becomes insensitive to the US value. We also found that the nature of the habitual response after extended Pavlovian training in crickets is not the same as that after extended instrumental training in mammals concerning the context specificity. Adaptive significance and evolutionary implications for our findings are discussed.